Historical background of municipal regulations of Bihar - Tripathi, Yogendra (Nagarlok: Quarterly Journal of Urban Affairs)
This is an article about History of Municipal Regulations of Bihar. As we know Bihar along with Orissa was part of Bengal which was governed under Bengal LSG Government Act, 1885. After first separation, Bihar and Orissa Municipal Act,1922 was formulated. After second separation, Orissa formulated its own Act in due course. The state of Bihar decided to upgrade Patna city Municipality into Municipal Corporation, as such separate Patna Municipal Corporation Act,1951 was formulated. Thus, two Acts came into operation, one for Municipal Corporation and another for Municipalities of Bihar. The amendments in both Acts were made as per provisions of 74th Constitutional Amendments in 1994. Later on a draft Municipal Act was circulated by the Government of India with the advice to incorporate the provisions of draft model in the existing municipal Acts or make separate Act as per draft. Instead of incorporating the provisions of draft in the existing municipal Acts, Bihar repealed its both municipal Acts and formulated a new Bihar Municipal Act, 2007, which is full of contradictions and totally against the spirit of 74th Amendment of the Constitution. So far about 250 amendments have been made in this Act and at least same number of amendments are further required for making this Act smoothly workable. - Reproduced
Keywords: Municipal regulations, Bihar municipal Act, 74th constitutional amendment